2006
DOI: 10.1016/j.otohns.2005.10.009
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ostiomeatal Complex Obstruction in Maxillary Fungus Ball

Abstract: B-3b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…concluded that their statistical data did not support the hypothesis that maxillary fungus ball is associated with ostiomeatal complex obstruction. They surmised that another as‐yet‐unexplained mechanism must be responsible for the disease . We found very few observable anatomical variations that could trigger ostiomeatal dysfunction in our series.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…concluded that their statistical data did not support the hypothesis that maxillary fungus ball is associated with ostiomeatal complex obstruction. They surmised that another as‐yet‐unexplained mechanism must be responsible for the disease . We found very few observable anatomical variations that could trigger ostiomeatal dysfunction in our series.…”
Section: Discussionmentioning
confidence: 53%
“…They showed that fungal ball was more frequent in rabbits with blockage of the maxillary ostium . Recently, Tsai et al . concluded that their statistical data did not support the hypothesis that maxillary fungus ball is associated with ostiomeatal complex obstruction.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In previous study [5], by comparing the Lund-McKay scores for the anterior ethmoidal and frontal sinuses of two groups of patients suffering from CRS and FB, it was demonstrated that obstruction of the OMC played a relevant role in the onset of rhinosinusitis, whereas a similar finding was not clearly demonstrable in the onset of an FB. Therefore, it was suggested that FB was not associated with OMC obstruction and that another factors would be responsible.…”
Section: Discussionmentioning
confidence: 99%
“…Eloy et al [4] suggested that sinus hypoventilation secondary to ostial dyspermeability plays an important role in trapping fungal spores and providing anaerobic conditions for the development of FB. Recently, Tsai et al [5] proposed some criticism of this hypothesis. By analyzing the Lund-McKay scores in paranasal sinus computed tomography (CT) scans, they demonstrated that obstruction of the OMC was not clearly demonstrable in the onset of an FB.…”
Section: Introductionmentioning
confidence: 99%